The ties that bind : Iran and Hamas' principal-agent relationship : a thesis presented in fulfilment of the requirements for the degree of Master of Arts in Politics at Massey University, Turitea, New Zealand - Thomson, Amy (Massey University, 2012)
The evolution of the Iran-Hamas relationship can be mapped using Principal-Agent analysis. It is a cost-benefit approach based on rational choice theory. In contrast to narrowly emphasising these actors‘ rhetoric, which is often used to mislead others, Principal-Agent analysis focuses on how these two actors react, or are perceived to react, to events to infer how their cost/benefit calculi change. This is in contrast to narrowly emphasising their rhetoric, which is often used to mislead others. The types of costs and benefits the actors receive from the relationship remain the same, although the changing geostrategic environment since the Iranian Revolution has increased and decreased their relative importance. For Iran, the relationship is most important for its ability to enhance legitimacy on the Arab Street, commit to retaliation, and plausibly deny responsibility helping to prevent conflict escalation with Israel. However, there are significant costs arising from the relationship for Iran because the effectiveness of Iran‘s control mechanisms is constrained by the influence of the Palestinian people over Hamas. Thus, when Palestinian preferences diverge from Iran‘s, the state‘s ability to control the organisation is limited. For Hamas, the funding and training it receives from the relationship are crucial. Despite this, the control mechanisms Iran attempts to place on Hamas can be damaging and contribute to divisions within the organisation when Palestinian preferences diverge from Iran‘s. Most of the time, however, the costs for Hamas are minor compared to other violent non-state actor/state Principal-Agent relationships.
Keywords: Iran; Hamas; Palestine; Middle Eastern politics